881. ACER OBTUSATUM: Sapindaceae. (12th September 2018) - Crowley, Dan
Summary: Acer obtusatum Waldst. & Kit. ex Willd. is illustrated and described. Its relationships with other species in section Acer series monspessulana, notably A. opalus Mill. are discussed.